2017
DOI: 10.1039/c7cc00668c
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a luminescent nanoprobe for hypoxia imaging in vivo via ratiometric and photoluminescence lifetime imaging microscopy

Abstract: A luminescent nanoprobe has been designed for detection of oxygen. The nanoprobe exhibits high sensitivity, selectivity and excellent reversibility, and has been employed for hypoxia imaging in vitro and in vivo by ratiometric and photoluminescence lifetime imaging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…In the first situation, no obvious interaction occurs between materials, where the self-luminous nanomaterial is only used as a reference for ratiometric detection. Currently, these frequently-used self-referenced luminous nanoparticles mainly consist of dye-embedded silica, 153, 154 gold nanoclusters (AuNCs), 155157 fluorescent bovine serum albumin nanoparticles, 158 Cdots, 159, 160 , silicon nanodots, 161 or quantum dots (QDs). 162, 163 Through a combination of the corresponding target-sensitive fluorescent dye units with unique responses to target analytes or molecular events, these dual-emission nanoparticle-dye nanoconjugates have been extensively applied for ratiometric sensing and imaging of diverse physical and physiological changes.…”
Section: Ratiometric Fluorescence Nanoprobesmentioning
confidence: 99%
“…In the first situation, no obvious interaction occurs between materials, where the self-luminous nanomaterial is only used as a reference for ratiometric detection. Currently, these frequently-used self-referenced luminous nanoparticles mainly consist of dye-embedded silica, 153, 154 gold nanoclusters (AuNCs), 155157 fluorescent bovine serum albumin nanoparticles, 158 Cdots, 159, 160 , silicon nanodots, 161 or quantum dots (QDs). 162, 163 Through a combination of the corresponding target-sensitive fluorescent dye units with unique responses to target analytes or molecular events, these dual-emission nanoparticle-dye nanoconjugates have been extensively applied for ratiometric sensing and imaging of diverse physical and physiological changes.…”
Section: Ratiometric Fluorescence Nanoprobesmentioning
confidence: 99%
“…Thus, such coupling reaction has little influence on fluorescence of nanomaterials and is widely used to prepare fluorescent nanocomposites. Indeed, some NCs‐based ratiometric fluorescent probes have been prepared by carbodiimide‐activated coupling reaction due to the fact that the surface of NCs usually contains a large amount of carboxyl groups or amino groups . For example, carboxyl‐functionalized Au NCs and amino‐functionalized carbon dots (CDs) can be directly bonded together to afford the assembled C‐dots‐AuNCs binary heterogeneous nanocomplexes via carbodiimide‐activated coupling reaction ( Figure a) .…”
Section: Sensor Designmentioning
confidence: 99%
“…Resultant DEFNs display ideal single‐excitation, dual‐emission with two well‐resolved, intensity‐comparable fluorescence peaks, and function in optical thermometry with high reliability and accuracy by exploiting the temperature sensitivity of their fluorescence intensity ratio (blue/red). Yu et al reported a dual‐emitting fluorescent probe by using EDC/NHS as an active agent to carry out carbodiimide‐activated coupling of Au NCs with amino‐containing iridium complexes …”
Section: Sensor Designmentioning
confidence: 99%
“…However, while TRAST is based on the readout of a strong fluorescence signal, the RTP signal is weak and susceptible to dynamic quenching by oxygen and trace impurities. Moreover, while TRAST can be based on a broad range of different fluorophores and even auto-fluorescent compounds, specific RTP probes are scarce and cannot easily be loaded into cells (Yu et al 2017 ). In contrast to RTP, TRAST is also not limited to imaging of triplet state parameters only.…”
Section: Transient-state (Trast) Spectroscopy/imaging To Exploit the mentioning
confidence: 99%